KONTROVERSI HUKUMAN MATI ANALISIS WACANA SASTRA KRITIS THE LIFE OF DAVID GALE FILM PERSPEKTIF SOCIOCULTURAL PRACTICE NORMAN FAIRCLOUGH - Abd Ghofur (IAIN MADURA, 2017)
This article is written in order to explain and to explore the hidden message contained in The Life of David Gale film, it is also to find out the reasons of the figures of Clearance and David Gale who deliberately sacrifice themselves [commit suicide] for an ideology that was fought by them, as well as try to uncover the ideology of the ruler who so impose a sentence of death in the name of justice, The theory of discourse analysis Norman Fairclough used by the writer to explain the hidden meaning in the text of [speech] contained in the film. Further, it was found that in the film the figures of Clearance with the deliberately suicidal, as part of efforts to prove that during this time the ruler of the [read: of the court] in giving a decision.